PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DAPAT MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II A SEKOLAH DASAR NEGERI 169 PEKANBARU - Yanti, Era; ', Erlisnawati; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Problem of this research is lowering result of learning IPA student, this matter is seen from average value of student that is 71,44. From 43 student people, tired assess above KKM as much 14 student people (33%), while student which not yet reached the value KKM as much 29 student people (67%), value KKM specified is 75. Pursuant to the problems require to be done by research of class action by applying model the study of discovery learning. Research [done/conducted] [in] SD N 169 Pekanbaru and executed at even semester of school year 2014/2015. With the student amount as much 43 one who is consisted of 23 men student and 20 woman student. This research is done as much 2 cycle. One cycle composed and 2 times meeting and 1 times Daily Restating (UH). Applied model the study of discovery learning improve the result learn the IPA student. From elementary score mount at cycle I of equal to 11,98% becoming 80,00. From elementary score to daily restating of II mount equal to 14,59% becoming 81,86%. Activities learn at Cycle I, second to first meeting until experience of the improvement 15,79% from 67,86% becoming 78,57%. [At] Cycle II, Make-Up of 8,33% became of [by] the meeting one until his second them than85,71% becoming 92,86%. Activities Student at Cycle I, second to first meeting until experience of the improvement 18,75% from 57,14% becoming 67,86%. At second to first cycle II meeting until experience of the improvement 13,64% from 78,57% becoming 89,29%. From inferential research result that applying model the study of discovery learning can improve the result learn the IPA of student of class of II A SDN 169 Pekanbaru.Keyword: Applying Model The Discovery Larning. Result Learn the IPA Student